Antimicrobial Properties of Monomeric and Dimeric Catanionic Surfactant System - Iwona Kowalczyk; Anna Koziróg; Adrianna Szulc; Anna Komasa; Bogumił Brycki (Molecules)
Cationic gemini surfactants are used due to their broad spectrum of activity, especially surface, anticorrosive and antimicrobial properties. Mixtures of cationic and anionic surfactants are also increasingly described. In order to investigate the effect of anionic additive on antimicrobial activity, experimental studies were carried out to obtain MIC (minimal inhibitory concentration) against E. coli and S. aureus bacteria. Two gemini surfactants (12-6-12 and 12-O-12) and two single quaternary ammonium salts (DTAB and DDAC) were analyzed. The most commonly used commercial compounds of this class, i.e., SDS and SL, were used as anionic additives. In addition, computer quantum mechanical studies were also carried out to confirm the relationship between the structure of the mixture and the activity. The obtained results of microbiological tests and quantum mechanical calculations are in agreement with each other and show the lack of synergism in catanionic mixtures in the case of antibacterial activity.